Municipal Ownership of Telephones in Great Britain - Holcombe, A. N. (Quarterly Journal of Economics, 1907)
Journal Article Municipal Ownership of Telephones in Great Britain Get access A. N. Holcombe A. N. Holcombe Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 4, August 1907, Pages 645–650, https://doi.org/10.2307/1883591 Published: 01 August 1907